Further observations on the life cycle and vectors of the haemosporidian Leucocytozoon tawaki and its transmission to the Fiordland crested penguin - Allison, F. R.; Desser, S. S.; Whitten, L. K. (Taylor & Francis, 1978)

(untitled)
Hepatic and renal schizonts are described from Fiordland crested penguin (Eudyptes pachyrh ynchus) chicks, and renal and splenic schizonts from mature birds. Ookinetes, oocysts, and sporozoites are described from the primary vector, Austrosimulium ungulatum. Penguin chicks are infected when 4-6 weeks old, Some observations are recorded on the biology of the vector in association with the bird.